Do voluntary sustainability standards for agricultural production contribute towards climate mitigation and adaptation? - Li, Yang (Nanyang Technological University, 2025)
Since the mid-1990s, Voluntary Sustainability Standards (VSSs) have rapidly expanded across sectors, with agriculture accounting for the largest share–152 out of over 400 active VSSs globally. As key governance tools in the global agricultural value chain, agricultural VSSs have been widely studied for their sustainability impacts. Yet, few have examined contributions to climate change mitigation and adaptation. This research addresses this gap by developing a classification framework and a scoring system to assess the contribution of six selected agricultural VSSs from the palm oil and cocoa sectors towards the Climate Objectives (COs). Findings indicate that the VSSs have limited contributions towards the COs, where the final scores of one or more climate pathways fall below the minimum benchmark of 1.5, indicating only some fulfilment of climate goals. Among the requirement categories, land management emerges as the strongest contributor to the COs, while others—such as crop management and social activities—show sector-specific variation. The results show that the current agricultural VSS designs tend to focus on building supporting assets and practices but lack direct, positive requirements that enhance carbon sequestration and climate resilience. Strengthening these areas could enhance the role of VSSs in advancing climate-resilient agriculture.